2003
DOI: 10.7863/jum.2003.22.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pregnancy-Associated Uterine Venous Plexus Thrombosis on the Basis of Transvaginal Sonography

Abstract: Focusing on the pelvic veins while performing a transvaginal sonographic study during pregnancy may reveal important findings, which may have clinical implications. The therapeutic treatment of uterine venous plexus thrombosis is controversial and still empirical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
2
15
1
Order By: Relevance
“…Objective criteria of vein distension are yet to be defined, and there is no normal range for pelvic vein diameter. In the case series of Leibovitz et al , vein diameter ranged from 10 to 16 mm, whereas in our case series the range was 5–15 mm.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Objective criteria of vein distension are yet to be defined, and there is no normal range for pelvic vein diameter. In the case series of Leibovitz et al , vein diameter ranged from 10 to 16 mm, whereas in our case series the range was 5–15 mm.…”
Section: Discussioncontrasting
confidence: 62%
“…This is a relatively common mutation affecting 2–5% of Caucasian populations and is associated with a modest increase in the background risk of thrombosis. Our findings are discordant with those of Leibovitz et al because these authors reported no thrombophilic defects in any of their patients. However, they do not specify which tests were carried out.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…After multidisciplinary consultation, we decided that the risk of bleeding outweighed the benefits of anticoagulant therapy in a woman with no proven thrombophilia. A previous report by Leibovitz et al 8 described four cases of uterine venous plexus thrombosis that were diagnosed in the first trimester. These cases, however, were not associated with cervical varices carrying an increased risk of bleeding, which facilitated the decision to initiate anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 98%
“…The basic management of RLVs during pregnancy is conservative because anesthesia and surgery may precipitate labor and RLVs will resolve spontaneously during the postpartum period because pelvic venous obstruction by the gravid uterus is relieved . However, close monitoring is critical because of the risk of rupture or acute thrombosis of the varices . In this case, breath‐holding was reduced to avoid increased intra abdominal pressure and a posterolateral episiotomy was performed to shorten second stage of labor and thereby reduce the risk of RLV rupture.…”
Section: Discussionmentioning
confidence: 99%